Locked and Loaded: Divergent Handgrip Tests as Surrogate Measures for One-Repetition Maximal Strength - S. Kyle Travis; Antonella V. Schwarz; Benjamin I. Burke (Biomechanics)
Background/Objectives: Despite widespread use in clinical and athletic settings, validity of handgrip strength (HGS) as a surrogate for maximal strength remains debated, particularly regarding how testing posture influences its predictive value. Moreover, while HGS is frequently considered a marker of ‘total strength’, this term is often vaguely defined, lacking a clear, performance-based framework. Therefore, this study investigates HGS as a potential surrogate measure for one-repetition maximum (1RM) performances in key compound lifts via back squat (BS), bench press (BP), deadlift (DL), and total (TOT), while accounting for variations in testing posture. Methods: Two distinct testing conditions were used to account for postural influences: Experiment 1 implemented high-output standing HGS (HGSSTAND) in 22 recreationally trained males [Wilks Score: 318.51 ± 44.61 au] vs. Experiment 2, which included low-output seated HGS (HGSSIT) in 22 competitive powerlifters [409.86 ± 46.76 au], with all testing immediately followed by 1RM assessment. Results: Correlational analyses identified the strongest association between HGSSTAND and 1RM DL (r = 0.693, BF10 = 106.42), whereas HGSSIT exhibited the strongest relationship with 1RM BP (r = 0.732, BF10 = 291.32). Postural effects had a significant impact on HGS outcomes (p < 0.001, η2 = 0.413), with HGSSTAND producing higher outputs than HGSSIT despite lower absolute strength 1RM capabilities. Conclusions: These findings emphasize the role of biomechanical specificity and neuromuscular engagement in grip strength assessments, indicating that HGS can function as a practical surrogate for maximal strength, though its predictive value depends on posture. Strength practitioners, sport scientists, and clinicians should consider these confounding factors when implementing HGS-based monitoring strategies.